PURITANICAL CHALLENGES IN ARTHUR MILLER’S “THE CRUCIBLE”. - Arunakumari , S (International Journal of Psychosocial Rehabilitation, 2021)
The Crucible, a play by Arthur Miller, was an adaptation of the Salem witch trials, which took place in the American province of Massachusetts Bay in 1692 and 1693. In the Crucible’s play, all characters are all based on real people who lived in Salem. Although there are several similarities to our own time in the play, it is full of ideas and attitudes that were unique to Salem, Massachusetts, in 1692. To clearly understand the play, some knowledge of Salem is required. As a result, the following information discusses essential Puritan beliefs and customs, as well as history including its historical Salem witch trials. In particular, Miller’s use of such Salem witch trials to critique upon this McCarthy trials in the 1950s discussed all these things throughout this paper.